Sixty days of head-down tilt bed rest with or without artificial gravity do not affect the neuromuscular secretome - Ganse, Bergita; Bosutti, Alessandra; Drey, Michael; Degens, Hans (Experimental cell research, 2021)
Artificial gravity is a potential countermeasure to attenuate effects of weightlessness during long-term spaceflight, including losses of muscle mass and function, possibly to some extent attributable to disturbed neuromuscular interaction. The 60-day AGBRESA bed-rest study was conducted with 24 participants (16 men, 8 women; 33 ± 9 years; 175 ± 9 cm; 74 ± 10 kg; 8 control group, 8 continuous (cAG) and 8 intermittent (iAG) centrifugation) to assess the impact of bed rest with or without daily 30-min continuous/intermittent centrifugation with 1G at the centre of mass. Fasting blood samples were collected before and on day 6, 20, 40 and 57 during 6° head-down tilt bed rest. Concentrations of circulating markers of muscle wasting (GDF-8/myostatin; slow skeletal muscle troponin T; prostaglandin E2), neurotrophic factors (BDNF; GDNF) and C-terminal Agrin Fragment (CAF) were determined by ELISAs. Creatine kinase activity was assessed by colorimetric enzyme assay. Repeated-measures ANOVAs were conducted with TIME as within-subject, and INTERVENTION and SEX as between-subject factors. The analyses revealed no significant effect of bed rest or sex on any of the parameters. Continuous or intermittent artificial gravity is a safe intervention that does not have a negative impact of the neuromuscular secretome. •Long-term bed rest with/without artificial gravity does not affect the neuromuscular secretome.•Serum concentrations of markers of muscle wasting are not affected by bed rest/artificial gravity.•C-terminal Agrin Fragment serum concentrations are not affected by bed rest/artificial gravity.•Human centrifugation during bed rest does not have a negative impact on the neuromuscular secretome.